2009
DOI: 10.1152/jn.91301.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Benzamil-Insensitive Salt Taste Receptor by Intracellular Ca2+, Protein Kinase C, and Calcineurin

Abstract: Ϫ6 M) or in TRPV1 KO mice. 32 Plabeling demonstrated direct phosphorylation of TRPV1 or TRPV1t in anterior lingual epithelium by PMA, cyclosporin A, or FK-506. PMA also enhanced the RTX-sensitive unilateral apical Na ϩ flux in polarized fungiform TRC in vitro. We conclude that TRPV1 or its variant TRPV1t is phosphorylated and dephosphorylated by PKC and PP2B, respectively, and either sensitizes or desensitizes the Bz-insensitive NaCl chorda tympani responses to RTX stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…These results suggest that NGCC specifically modulates NaCl and glutamate responses without affecting responses to representative sweet, bitter, sour, and non-Na ϩ salt taste stimuli. Lyall et al 2006Lyall et al , 2009. We have previously shown that 10 mM CaCl 2 by itself does not elicit a CT response.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…These results suggest that NGCC specifically modulates NaCl and glutamate responses without affecting responses to representative sweet, bitter, sour, and non-Na ϩ salt taste stimuli. Lyall et al 2006Lyall et al , 2009. We have previously shown that 10 mM CaCl 2 by itself does not elicit a CT response.…”
Section: Resultsmentioning
confidence: 96%
“…The major part of the study involved recording CT nerve responses in rats so that the data from NGCC can be compared with the already published data in the rat from several other TRPV1t modulators (Katsumata et al 2008;Lyall et al 2004Lyall et al , 2005aLyall et al , 2005bLyall et al , 2005cLyall et al , 2007Lyall et al , 2009Lyall et al , 2010aTreesukosol et al 2007). We also monitored CT responses in WT (C57BL/6J) and homozygous TRPV1 KO [B6.129S4-Trpv1 tmijul , N10F19 (02-JAN-10); Jackson Laboratory, Bar Harbor, ME] mice to demonstrate that the effect of NGCC is species independent but is dependent upon the TRPV1 gene product (Lyall et al , 2005a.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that CaN has a regulatory effect and potential physical interaction with intracellular Ca 2ϩ release channels (4). CaN has also been shown to oppositely modulate PKC substrates like the transient receptor potential vanilloid-1 (TRPV1) channels in chorda tympani taste neurons (28), the myristoylated alanine-rich C kinase substrate (MARCKS), and growth-associated protein43 (GAP43) in the rat hippocampus (47) and L-type Ca 2ϩ channels in vascular SMCs (30). Taken together, in the current study, we performed a series of pharmacological and genetic studies to test a novel hypothesis that CaN is a suitable phosphatase of interest in the regulation of local Ca 2ϩ signaling and associated contraction in ASMCs, and the role of CaN may also be specifically mediated by RyR1.…”
mentioning
confidence: 99%